1991
DOI: 10.1002/bip.360310102
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐ and salt‐induced coil–helix transition of alkali metal salts of poly(L‐glutamic acid) in aqueous organic solvents

Abstract: SYNOPSISThe coil-helix transition has been studied for alkali metal salts of poly (L-glutamic acid) ( P L G ) , i.e., PLGLi, -Na, -K, and -Cs, in aqueous organic solvent systems. Dependence of the transition on the solvent composition has been qualitatively discussed in terms of the solvent dielectric constant D , Gutmann's acceptor number AN, and water activity G . The helix formation induced by addition of alkali chlorides has also been studied. The sharpness of the transition has been interpreted as a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…This means that ion-pairs formed between 1COO -groups and Na + are more stable than those with Cs + . In fact, many studies on counterion binding showed that carboxylate anions prefer smaller counterions 13,14) like Na + and Li + to larger ones like K + and Cs + . This has been interpreted as an empirical rule 15) , i. e., interactions between two solvent-structure makers (smaller ions) or two structure breakers (larger ions) are stronger (attractive) than those between a structure maker and a breaker.…”
Section: )mentioning
confidence: 99%
“…This means that ion-pairs formed between 1COO -groups and Na + are more stable than those with Cs + . In fact, many studies on counterion binding showed that carboxylate anions prefer smaller counterions 13,14) like Na + and Li + to larger ones like K + and Cs + . This has been interpreted as an empirical rule 15) , i. e., interactions between two solvent-structure makers (smaller ions) or two structure breakers (larger ions) are stronger (attractive) than those between a structure maker and a breaker.…”
Section: )mentioning
confidence: 99%
“…Exposure to light and the consequent photoconversion of the side chains to the apolar spiro form makes the macromolecules adopt the a-helix conformation. Addition of methanol to aqueous solutions is known to induce the coil -helix transition in poly ( a-amino acid) s having charged side chains, such as sodium poly ( L-glutamate ) 46 and poly (L-lysine ) hydr~chloride.~' At a sufficiently high concentration of methanol (> 40% ) , therefore, an analogous solvent effect should allow the photochromic polypeptide to stay in a-helix in the dark as well (photochromic units present as charged species 111) .…”
Section: Spiropyran Salts As Side-chain Photochromic Unitsmentioning
confidence: 99%
“…Counterion binding of polyelectrolytes is an essential factor for ordered structures of biopolymers such as DNA,1 proteins,2 and charged polysaccharides3 and their functions in vivo as well as for the volume phase transition of synthetic polymer gels4, 5 in vitro. We have been studying counterion binding of some synthetic6, 7 and biopolyelectrolytes8–10 in water/organic solvent mixtures and found marked ion‐ and solvent‐specificities for binding and the resultant structure transition, such as gel collapse11–13 due to ion‐cluster formation and the coil–helix transition of charged polypeptides. For example, α ‐helix conformation of sodium poly(L‐glutamate) (PLGNa) was stabilized in aqueous solutions containing an organic solvent in a higher ratio, for example, ≧ 70 vol % ethanol, while the stability was significantly reduced for the potassium salt or in aqueous t ‐butanol 8.…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying counterion binding of some synthetic6, 7 and biopolyelectrolytes8–10 in water/organic solvent mixtures and found marked ion‐ and solvent‐specificities for binding and the resultant structure transition, such as gel collapse11–13 due to ion‐cluster formation and the coil–helix transition of charged polypeptides. For example, α ‐helix conformation of sodium poly(L‐glutamate) (PLGNa) was stabilized in aqueous solutions containing an organic solvent in a higher ratio, for example, ≧ 70 vol % ethanol, while the stability was significantly reduced for the potassium salt or in aqueous t ‐butanol 8. The ion‐specificity (Cs + ≪ K + < Li + < Na + ) for the helix stabilization was comparable to that in cation–carboxyl anion binding,14, 15 and the solvent specificity was explained in terms of the dielectric constant, water activity, and Gutmann–Mayer's Acceptor Number (AN)16 of the relevant solvents.…”
Section: Introductionmentioning
confidence: 99%